BOOK REVIEW: CORPUS LINGUISTICS AND SECOND LANGUAGE ACQUISITION: PERSPECTIVES, ISSUES, FINDINGS - Samsudin, Samsudin; Sukarismanti, Sukarismanti (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2024)
This article discusses the application of corpus linguistic methods in second language acquisition (SLA) research. It highlights the significance of utilizing native and learner corpora, along with automated tools for corpus annotation and analysis, to explore various aspects of SLA. The article is based on a book titled